Pengembangan Tenant Universitas Muslim Nusantara Al Washliyah di Masa New Normal - Shita Tiara; Debbi Chyntia Ovami; Siti Fatimah Hanum (Asosiasi Dosen Akuntansi Indonesia, 2020)
Higher education has a role to motivate students and undergraduates to become young entrepreneurs and is part of one of the factors driving entrepreneurial growth. The purpose of this activity is to produce independent science and technology-based entrepreneurs who are ready to work in society. The approach method in the KDP program is the Participatory Action Learning System (PALS). The targets that were the main targets of PPK UMN Al Washliyah activities were students, PKM and Alumni of UMN Al Washliyah. Entrepreneurship Development Program activities by providing entrepreneurship guidance, motivation, training, mentoring, and consultation. The PPK UMN Al Washliyah activity in 2020 is the third year of carrying out PPK activities and has carried out activities including introducing entrepreneurship and motivating students to become entrepreneurs in Islamic entrepreneurship public lectures, recruiting tenants for PPK UMN Al Washliyah participants, entrepreneurship training, enhancement entrepreneurial skills with internships, practice and visits to business premises, providing business capital in the form of supporting equipment and consumables, product exhibitions, and evaluation of tenant work activities. The PPK UMN Al Washliyah activity in the third year has produced 20 (twenty) independent entrepreneurs. Universitas Muslim Nusantara Al Washliyah has collaborated to facilitate the development of tenant entrepreneurship with several institutions or businesses. Muslim Nusantara Association (UMN) Al Washliyah to produce independent science and technology-based entrepreneurs who are ready to work in society.